BAHAYA MEROKOK PADA REMAJA - Gobel, Satria; Pamungkas, Rian Adi; Abdurrasyid, Abdurrasyid; Sari, Rista Puspita; Safitri, Adelia; Samran, Samran; Aponno, Vica Agatha L; Fadilah, Ika; Olivia, Trinil; Pina M, Firza; Tiwery, Susanty M (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
This activity is a form of application in community service carried out by students. Based on the results of surveys, interviews and observations, it was found that the problem of adolescents who smoke. Smoking is the inhalation of substances that are harmful to the body that affect health. Based on the results of a questionnaire, adolescents who smoke are 28.6% 15 years old, 22.9% 16 years old, 31.4% 17 years old, 8.6% 18 years old, 8.6% 19 years old. Meanwhile, based on gender, 100% of adolescents who smoke are male. The method used in the implementation of Health Education is direct and DARING by using an online zoom application. Health education is an application or application of education in the health sector. The results of this Health Education activity have increased the knowledge of adolescents about the dangers of smoking by 80% and 80% of adolescents wish to quit smoking.Â Keywords : smoking, health education, the dangers of smoking